Effects of Food Environments and Eating Environments on Consumers' Food Consumption Volume. (28th May 2019) - Kuo, Su-Hui; Lin, Hung-Chou
Abstract : Even though the influences of eating environments and the food environments on consumption have been discussed, little has been done to examine whether the food environments would be influenced by the eating environments. For example, the size of plate has been proved to have impact on consumers' consumption volume; it is still unknown whether the eating environment would interact with the food environment and in turn influences consumers' consumption volume. This research explores the underlying mechanisms how consumers are influenced by the size of bowl when they consume food. In addition, eating environments are also incorporated to discuss their effects on the relationship between bowl size and consumers' consumption volume. The results indicate people who receive a large bowl with large chopsticks exhibit greater food consumption than those who receive a small bowl with small chopsticks. However, when people use tableware inconsistently, they exhibit similar food consumption. Under bright illumination, people given large bowls with large chopsticks exhibit greater food consumption than those given small bowls with small chopsticks; however, when people use inconsistently sized tableware, they exhibit similar food consumption. Under dim illumination, no significant differences in food consumption amount are evident in association with bowl and chopstick sizes.